The prevention of plaque re-growth by toothpastes and solutions containing block copolymers with and without polypeptide - Claydon, N. C.; Addy, M.; Newcombe, R.; Moran, J. (Journal of clinical periodontology, 2005)
Background/Aims: Chemicals which have a direct effect at inhibiting or reducing bacterial adherence to tooth surfaces may subsequently inhibit plaque growth and reduce gingival inflammation. This study investigated whether two anti‐adherent systems could inhibit plaque re‐growth in the mouth when rinsed as a solution or as a toothpaste slurry. Methods: A total of 21 subjects took part in a partially blind, seven cell cross‐over study which compared the effects on plaque re‐growth of a binary system containing block copolymers, a ternary system containing block copolymers and polypeptide, both used as toothpaste slurry rinses, their corresponding solution rinses, a conventional fluoride toothpaste rinse, a positive control chlorhexidine rinse and a negative water control. Following a dental prophylaxis subjects then rinsed with 10 ml of one of the test products for 1 min. twice a day over a 4‐day period. Throughout each trial period the subjects were not permitted to use any other forms of oral hygiene. On the fifth day (96 h), the volunteers returned to the clinic, and plaque was assessed by (1) plaque index and (2) plaque area following disclosing with a food dye. The test phase of the trial was repeated for each agent and was followed by a 10‐day “washout” period. Results: Essentially neither of the anti‐adherent systems inhibited plaque re‐growth, whether administered in a toothpaste slurry or solution compared with the controls. If anything, neither of the test pastes were as effective as the marketed commercial paste (p<0.001). As expected plaque recorded following use of the chlorhexidine rinse was significantly less than that seen with any of the other rinses (p<0.001). Conclusions: Using this 4‐day plaque re‐growth model, the findings of this study failed to show any benefit in using the anti‐adherent systems, either in a rinse or toothpaste, with the aim of inhibiting or reducing plaque formation.